Pengaruh Harga, Promosi dan Kualitas Produk Terhadap Minat Beli Masyarkat Terhadap Smartphone Merk Cina - Aditya Krisna Ariyanto; Ginanjar Rahmawan (Widya Manajemen, 2021)
The implementation of the following research is to find out the effect of price, promotion, and product quality on people's buying interest in Chinese brand smartphones. The population used in the implementation of the study were students at the STIE Surakarta campus, and the sample of this study was 88 people. Researchers chose accidental sampling technique used in the implementation of the following research. The data analysis of this study used multiple linear regression analysis where the data processing used the Statistical Package for Social Science (SPSS) program. The results of his research show that it has a significant effect on the price on purchase intention which is explained by the value which is 0.028 lower than 0.05, then the effect of promotion on purchase intention also has a significant effect because it has a value of 0.000 less than 0.05, then that is. Finally, the effect of product quality on purchase intention has a significant effect because it is explained by the result that the value of 0.000 is lower than 0.05.